2021
DOI: 10.1186/s13023-021-01816-2
|View full text |Cite
|
Sign up to set email alerts
|

Patient and caregiver experiences of living with acute hepatic porphyria in the UK: a mixed-methods study

Abstract: Background This study used quantitative and qualitative research methods to analyze how acute hepatic porphyria (AHP) affects patients with varying annualized porphyria attack rates. The overall impact of AHP on patients and caregivers, including their quality of life, was explored. The nature and treatment of acute attacks, experiences of long-term heme arginate treatment and access to other appropriate treatment, and the extent of and treatment for chronic symptoms were also investigated with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Acute hepatic porphyrias (AHP) are a group of rare genetic diseases of heme biosynthesis. 1 , 2 Four types of acute porphyria have been identified, each having unique enzymatic defects: acute intermittent porphyria (AIP), hereditary coproporphyria (HCP), variegate porphyria (VP), and ALAD (5′‐aminolevulinic acid dehydratase) deficiency porphyria (ADP). 1 Among these AHP types, AIP is the most common, with a calculated prevalence of 5.9 per 1 million in European countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute hepatic porphyrias (AHP) are a group of rare genetic diseases of heme biosynthesis. 1 , 2 Four types of acute porphyria have been identified, each having unique enzymatic defects: acute intermittent porphyria (AIP), hereditary coproporphyria (HCP), variegate porphyria (VP), and ALAD (5′‐aminolevulinic acid dehydratase) deficiency porphyria (ADP). 1 Among these AHP types, AIP is the most common, with a calculated prevalence of 5.9 per 1 million in European countries.…”
Section: Introductionmentioning
confidence: 99%
“…20 For patients, caregivers, and clinicians, these studies and others provide insight into the extent of the impact of AHP beyond clinical symptoms. 21 While prior studies evaluated a limited set of patient-reported outcome (PRO) tools among patients within particular countries, 2,[22][23][24] there is still a lack of understanding of the full burden of AHP, especially in a study including a diverse set of patients across the globe. The present study was designed to assess the full spectrum of the AHP patient's well-being and unmet emotional, mental, and physical needs across countries and regions of the world.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research into the burden of recurrent AHP found similar symptoms and impacts to those described here. For instance, pain, nausea, fatigue, and aspects of neuropathy were considered key chronic symptoms and sleep difficulties, inability to work, negative financial impact, difficulty walking, and decreased socialization were main impacts identified in previous studies [ 19 , 30 ]. Only one study was identified that examined a population broadly similar to the patient population examined here [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Along with these, pain management, respiratory support, intensive physiotherapy, nutritional support, medication review for safety in porphyria, mental health support [15], and patient and caregiver education should be continued in parallel. Organizations support groups such as the National Acute Porphyria Service, National Organization for Rare Disorders, and the British Porphyria Association provide valuable resources [16].…”
Section: Figure 5: Heme Synthesis Pathwaymentioning
confidence: 99%